The relationship between periodontitis and preeclampsia: A systematic review - Amir hossein Fathi; Elmira Fardi; Ulduz Zamani Ahari; Misa Naghdipour Mirsadeghi; Farzaneh Oraie (Mashhad University of Medical Sciences, 2021)
Introduction: For various reasons, such as the lack of focus on studies on the relationship between periodontitis and preeclampsia, as well as the small number of people who develop preeclampsia after periodontitis, scattered research has been conducted in different parts of the world. They are not collected regularly so that researchers can have the results together; therefore, this study was performed with aim to investigate the relationship between periodontitis and preeclampsia to assess the role of periodontitis as an independent factor in preeclampsia.Methods: This systematic review study was performed in 2020 with searching for keywords of preeclampsia, periodontitis, periodontal, pregnancy complications, pregnancy outcomes, relationship and treatment (Based on Mesh) in databases of PubMed, Scopus, Google Scholar, SID, IranDoc, Web of Sciences, Science Direct, OVID and Springer without time limit among the published articles in Persian and English and their information was recorded in a checklist designed for this research. Results: Out of 759 articles found, only 9 (6 cohort articles and 3 clinical trial articles) were included in the study. Five cohort articles confirmed that periodontitis could lead to preeclampsia, and three clinical trial articles found no association between treatment of periodontitis and reduction of preeclampsia.Conclusion: Periodontitis can be effective in preventing diseases during pregnancy; the role of this variable in preeclampsia has not been determined precisely, but the results of studies suggest that periodontitis may lead to preeclampsia; the results of this study should be used with caution.